Scorpion venom and its adaptive role against pathogens: a case study in Centruroides granosus Thorell, 1876 and Escherichia coli - Gálvez, Dumas; Bonilla, Eleodoro; Vega, Carlos (Frontiers in Arachnid Science, 2023)
Scorpion venoms have been studied extensively, mostly aimed at applications for human health, with strong evidence of antimicrobial properties. However, ecological studies on the adaptive role of these antimicrobial properties have been mostly neglected. Here, this study investigated in the scorpion Centruroides granosus Thorell, 1876 (Scorpiones: Buthidae) whether the venom provided protection against consumption of crickets injected with a pathogenic strain of the bacteria Escherichia coli. Preventing venom injection when consuming contaminated prey decreased scorpion survival as compared to their controls (PBS injection) and scorpions that injected the venom. Scorpions that injected the venom did not show lower survival when consuming contaminated prey as compared to their own control, and there was no difference in survival for the controls of scorpions that were prevented or allowed to inject the venom. Altogether, the results highlight the adaptive benefit of the venom for scorpions when coping with potentially hazardous prey. The implications of the findings are discussed, and this work seeks to encourage more work on the neglected field of venom evolutionary ecology of scorpions and other arthropods.